Fenomena Cyber Public Relations pada Lembaga Pemerintah Non Kementerian: (Studi kasus Aktivitas Cyber Public Relations pada Badan Pengkajian dan Penerapan Teknologi/ BPPT) - Ariyanti, Dian Metha (Magenta | Official Journal STMK Trisakti, 2018)
The phenomenon of Cyber Public Relations in Non-Ministerial Governance Institutions is an interesting thing to be studied. This study raises case studies at one of these institutions, the Agency for the Assessment and Application of Technologies (BPPT), which was awarded as Top IT Institution in 2017. The purpose of this research is to see how far the IT-based institutions perform Cyber Public Relations activities to publish performance and enhance corporate image in the eyes of the public. This research uses qualitative research approach and descriptive research type. Data collection was obtained through observation, interview, and documentation. The findings of research that the dissemination of information conducted public relations BPPT has been using Internet-based media such as websites and utilize social media such as twitter, facebook, instagram, and youtube to publicize. Despite having many advantages, Cyber Public Relations activity is still constrained internet access problems, human resources and also bureaucratic policy.